Regulating the stemness of mesenchymal stem cells by tuning micropattern features. Issue 1 (23rd November 2015) - Wang, Xinlong; Nakamoto, Tomoko; Dulińska-Molak, Ida; Kawazoe, Naoki; Chen, Guoping
Abstract : The stemness of MSCs was significantly influenced by cell morphogenesis regulated by micropatterns, and was always accompanied with change of nuclear activity and cytoskeleton mediated nanomechanics. Abstract : There is increasing evidence that microstructures play an important role in the maintenance of the multipotency of stem cells. However, it is not clear how micropatterns affect the stemness of stem cells. We prepared micropatterns of different sizes, shapes and aspect ratios and used them for the culture of mesenchymal stem cells (MSCs) derived from human bone marrow to investigate their influence on the stemness of MSCs at the single cell level. The percentage of cells positively stained by stem cell markers decreased with increasing spreading area and aspect ratio. However, the cellular geometry controlled by the geometrical micropatterns had no significant influence on the expression of stem cell markers. The change in the stemness of stem cells was accompanied by changes in the nuclear activity and cytoskeleton. The nuclear activity increased with increasing spreading area and aspect ratio. The actin filament structure was significantly influenced by the spreading area and aspect ratio. The cells became stiffer when they had sufficient area to spread into or when they were elongated. These results suggest that controlling the cell morphology by micropatterns may be useful in varying the stemness of MSCs. This study will contribute to the design of materials for maintaining the multipotency of stem cells, enhancing their clinical application and helping to reveal the processes taking place under conditions of stem cell quiescence in vivo .